Multi-walled carbon nanotubes trigger lysosome-dependent cell death (pyroptosis) in macrophages but not in neutrophils. Issue 9 (21st October 2021) - Keshavan, Sandeep; Gupta, Govind; Martin, Sebastin; Fadeel, Bengt
Abstract: Carbon nanotubes (CNTs) have been extensively investigated, and several studies have shown that multi-walled CNTs can trigger inflammation and fibrosis in animal models. However, while neutrophils are involved in inflammation, most in vitro studies have addressed macrophages. Here we explored the impact of three MWCNTs with varying morphology (i.e. long and rigid versus short and/or tangled) on primary human macrophages and macrophage-differentiated THP-1 cells versus primary human neutrophils and neutrophil-differentiated HL-60 cells. We found that long and rigid MWCNTs triggered caspase-dependent cell death in macrophages, accompanied by NLRP3 inflammasome activation and gasdermin D (GSDMD)-mediated release of pro-inflammatory IL-1β. The release of IL-1β was suppressed by disulfiram, an FDA-approved drug known to act as an inhibitor of membrane pore formation by GSDMD. Evidence of autophagic cell death was noted in macrophages exposed to higher concentrations of the long and rigid MWCNTs. Furthermore, lysosomal damage with cytosolic release of cathepsin B was observed in macrophages exposed to the latter MWCNTs. On the other hand, there was little evidence of uptake of MWCNTs in neutrophils and the cells failed to undergo MWCNT-triggered cell death. Our studies have demonstrated that long and rigid MWCNTs trigger pyroptosis in human macrophages.